Calcium and regulation of the mitochondrial permeability transition. (March 2018) - Giorgio, Valentina; Guo, Lishu; Bassot, Claudio; Petronilli, Valeria; Bernardi, Paolo
Graphical abstract: Highlights: Permeability transition pore (PTP) is a Ca2+-activated channel whose prolonged openings can lead to depolarization, Ca2+ release and cell death. Our working hypothesis is that the channel forms from F-ATP synthase dimers following Ca 2+ -binding to the catalytic site. Ca 2+ competes with PTP-inhibitory Mg 2+, and is an essential permissive factor for PTP opening. Ca 2+ binding could cause a conformational change transmitted via OSCP to the peripheral stalk and the the inner membrane. Abstract: Recent years have seen renewed interest in the permeability transition pore, a high conductance channel responsible for permeabilization of the inner mitochondrial membrane, a process that leads to depolarization and Ca 2+ release. Transient openings may be involved in physiological Ca 2+ homeostasis while long-lasting openings may trigger and/or execute cell death. In this review we specifically focus (i) on the hypothesis that the PTP forms from the F-ATP synthase and (ii) on the mechanisms through which Ca 2+ can reversibly switch this energy-conserving nanomachine into an energy-dissipating device.